Protein profile in cells exposed to nonthermal radiofrequency field. - Xu, Lanbing. (2009)
This project focus on the in vitro study of changes in protein profile in cells after exposure to radiofrequency from telecommunication devices and evaluate the change in protein profile with relevance to the effects on human health. The experiment was conducted at 37oC (±0.5oC) and the cell samples were subjected to 10 or 40 minutes of exposure to radiofrequency of GSM 900MHz at 41V/m. Using LC/MS, the proteins present in the cell samples were analyzed and the protein concentration of radiated cells were compared against sham samples. There were visible changes in relative abundance of Histone 2A and 4, which can be linked to possible DNA damages. However, there were no evidence of changed protein level in metabolic proteins and it is concluded that there is no short term non-thermal effect of radiofrequency field on cells.